Physicochemical properties of large-ring cyclodextrins (CD10-CD17)[1] - Satoru Motohama; Eiji Ishii; Tomohiro Endo; Hiromasa Nagase; Haruhisa Ueda; Takeshi Takaha; Shigetaka Okada (ՀՀ ԳԱԱ հրատ.)
Cyclomaltodecaose (CD10), cyclomaltoundecaose (CD12), cyclomaltotridecaose (D13), cyclomaltotetradecaose (CD14), cyclomaltopentadecaose (CD15), cyclomaltohexadecaose(CD16), and cyclomaltoheptadecaose (CD17) are cyclic oligosaccharides composed of 10, 11, 12, 13, 14, 15, 16 and 17 D-glucose units, respectively.
Keywords: Biology; Biochemistry